LA EVOLUCIÓN DE LAS RETRANSMISIONES DEPORTIVAS EN TELEVISIÓN A TRAVÉS DE LAS NUEVAS TECNOLOGÍAS: EL FÚTBOL COMO PARADIGMA EN ESPAÑA - Dra. Vanessa ROGER MONZÓ (Fonseca, Journal of Communication, 2023)
Sports broadcasts on television are events that take place outside the premises of program production centers, but are issued by the broadcaster through the coverage of a mobile unit. The first broadcasts of football matches in Spain were conducted with three cameras. Since then,developments in the planning of these sporting events has been marked by the introduction of new technologies.